Effects of Asia's currency crisis on the chinese economy : should China devalue? - Chua, Lee Cheng. (2008)
This paper thus seeks to find out the impact of ASEAN-4's depreciation on the Chinese economy and whether a devaluation would be effective in improving her exports, by running three regression models using time series data.